Clinical and functional results of radiofrequency ablation and microwave ablation in patients with benign thyroid nodules - UĞURLU, MUSTAFA ÜMİT (SAUDI MED J, 2021)
Objectives: To determine how well ultrasound-guidance percutaneous radiofrequency ablation (RFA) and microwave ablation (MWA) performed for benign symptomatic thyroid nodules in terms of clinical and functional outcomes. Methods: Patients who had a thyroid nodule-linked symptoms acting as dysphagia, cosmetic issues, pain, a foreign body sense, hyperthyroidism secondary to autonomous nodules, or concern of malignancy were involved in the study. The primary was the comparison in symptom scores obtained at 1, 3, and 6 months after RFA and MWA. The volume alterations in nodules and alterations in thyroid gland functions were secondary objectives. Results: This prospective study carried out from November 2014 and January 2017 at the General Surgery Department, Marmara University, Faculty of Medicine, Istanbul, Turkey included a total of 100 nodules (50% MWA, 50% RFA). There were statistically significance in pain scores, dysphagia scores, and foreign body sensation scores at 1, 3, and 6 months after therapy in both ablation groups (p=0.0006, p=00004, p=0.0005). At the same time, there were statistically significant reductions in size and volume of the nodules for RFA and MWA (p=0.0004, p=0.0003). There was no significant difference between the RFA and MWA groups' cosmetic scoring and volume changes (p=0.68, =0.43). Conclusion: Alternative therapies for benign symptomatic thyroid nodules include RFA and MWA. The findings of this research revealed that both approaches are safe and effective.
Keywords: thyroid; benign nodule; radiofrequency ablation; microwave ablation; symptom score; GUIDED PERCUTANEOUS RADIOFREQUENCY; RADIOIODINE THERAPY; FOLLOW-UP; EFFICACY; SAFETY; COMPLICATIONS; FEASIBILITY; COMBINATION; DISEASE